Synthesis report of two workshops conducted on Engaging Ethiopian Universities in Up-scaling Community-Based Breeding Programs - Abegaz, Solomon; Getachew, Tesfaye; Belay, Berhanu; Solomon, Dawit; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Two consecutive workshops were conducted on 20th and 27th of July 2021 at Bahir Dar and Debrezeit, respectively. The workshops were aimed at engaging Ethiopian Universities in up-scaling of community based breeding programs (CBBP) through incorporation of CBBP in animal breeding curriculum and being involved in the implementation of CBBP in the vicinity of the Universities. In the first workshop representatives of ten Universities namely: Debrebirhan, DebreMarkos, Gondar, Woldiya, Mekdela, Wollo, Bahir Dar, Enjibara, DebreTabor and Debark have participated in the discussion which lasted one day. Additionally representatives of the regional research institute, the notational Animal Genetic Improvement Institute (NAGII), the regional livestock agency and the national and regional coordinators of the Livestock and Fisheries Sector Development Project (LFSDP) have participated in the workshop. The venue for the first workshop at Bahir Dar was Naky Hotel. In the second workshop which took place at Debrezeit Gold Mark Hotel, a total of eleven Universities namely: Haramaya, Hawassa, Jimma, Bonga, Wolita Sodo, Arsi, Wollega, Wachemo, Mizan tepi, Assossa, and Semera have participated. Here also the regional livestock agencies of Oromia and Southern Region, representatives of research institutions and centers, NAGII, and LFSDP have taken part in the workshop.